First-Best and Second-Best Regulation of Solid Waste under Imperfect Competition in a Durable Good Industry - Marco Runkel (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1999)
Under the assumption of imperfect competition in a durable good industry, the present paper investigates the efficient regulation of solid waste which causes environmental damage at the end of the product's life. It turns out that the second-best waste tax falls short of the marginal environmental damage if the producers rent their products but may also exceed the marginal damage if the producers sell their products. If in the sales case the industry is regulated with waste taxes and stock subsudies then the first-best tax-subsidy scheme also contains a waste tax which deviates from the marginal damage, in general. Under monopoly this tax unambiguously exceeds the marginal damage. Furthermore, the analysis provides a further reason why the Swan independence result generally doesn't hold in rental markets.
Keywords: L12; L13; H21; Q28; 330; Abfallabgabe; Optimale Besteuerung; Dauerhaftes Konsumgut; Unvollkommener Wettbewerb; Umweltökonomik; Theorie